MEDIA SOSIAL DAN TRANSFORMASI PENDIDIKAN DI SEKOLAH DASAR : KAJIAN LITERATUR DALAM PERSPEKTIF SOSIOLOGI PENDIDIKAN - Nurrahman, Yusuf; Arif Fahrudin; Arif Rumiyadi; Djalal Fuadi; Sigit Haryanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of social media has significantly transformed educational practices in public elementary schools. Social media is no longer used solely for communication but has also become a learning medium, a platform for social interaction, a tool for school promotion, and a bridge connecting teachers, students, parents, and the wider community. However, its use also presents several challenges, including learning distractions, excessive dependence on digital devices, limited digital literacy, and unequal access to technology. This study aims to analyze the influence of social media on education in public elementary schools from the perspective of Educational Sociology. The study employed a Systematic Literature Review (SLR) using the PRISMA 2020 framework. Data were collected from 30 articles published in nationally accredited Indonesian journals indexed in SINTA 1–5. Following the identification, screening, eligibility assessment, and inclusion stages, 20 relevant studies were selected for analysis. The findings reveal that social media contributes positively to learning accessibility, student motivation, school-family communication, digital literacy, and the development of critical thinking and collaborative skills. Nevertheless, social media may also generate negative effects when used without adequate supervision and digital literacy support. Therefore, schools should establish educational, safe, and well-regulated social media policies. Social media can serve as an effective instrument for educational transformation when integrated thoughtfully into the learning process and aligned with educational goals.